Thermosensitive poly(organophosphazene)-paclitaxel conjugate gels for antitumor applications - Chun, Changlu; Lee, Sun Mi; Kim, Sang Yoon; Yang, Han Kwang; Song, Soo-Chang (ELSEVIER SCI LTD, 2009)
A poly(organophosphazene)-PTX conjugate was synthesized by a covalent ester linkage between M and carboxylic acid-terminated poly(organophosphazene), which can be readily modified by various hydrophobic, hydrophilic, and other functional substitutes. The physicochemical properties, hydrolytic degradation and PTX release behaviors of the polymer-PTX conjugate were characterized, in addition to the in vitro and in vivo antitumor activities. The aqueous solutions of these conjugates showed a sol-gel transition behavior that depended on temperature changes. The in vitro antitumor activity of the polymer-M conjugate was investigated by an MTT assay against human tumor cell lines. From the in vivo antitumor activity studies with tumor-induced (xenografted) nude mice, the polymer-paclitaxel conjugate hydrogels after local injection at the tumor site were shown to inhibit tumor growth more effectively and longer than paclitaxel and saline alone, indicating that the tumor-active paclitaxel from the polymer-PTX conjugate hydrogel is released slowly over a longer period of time and effectively accumulated locally in the tumor sites. These combined observations suggest that this poly (organophosphazene)-PTX conjugate holds promise for use in clinical studies as single and/or combination therapies. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: DRUG-DELIVERY SYSTEMS; AMINO-ACID ESTERS; CANCER-THERAPY; SIDE-GROUPS; PACLITAXEL; GLYCOL); POLYMERS; PRODRUGS; POLYPHOSPHAZENES; TEMPERATURE